Endoscopic Endonasal Petrosectomy: Anatomical Investigation, Limitations, and Surgical Relevance. Issue 5 (3rd May 2019) - Borghei-Razavi, Hamid; Truong, Huy Q; Fernandes Cabral, David T; Sun, Xicai; Celtikci, Emrah; Wang, Eric; Snyderman, Carl; Gardner, Paul A; Fernandez-Miranda, Juan C
Abstract: BACKGROUND: The endoscopic endonasal approach (EEA) was recently added to the neurosurgical armamentarium as an alternative approach to the petrous apex (PA) region. However, the maximal extension, anatomical landmarks, and indications of this procedure remain to be established. OBJECTIVE: To investigate the limitations and suggest a classification of PA lesions for endoscopic petrosectomy. METHODS: Five anatomical specimens were dissected with EEA to the PA. Anatomical landmarks for the surgical steps and maximal limits were noted. Pre- and postprocedural computed tomographic scan and image-guidance were used. Relevant surgical cases were reviewed and presented. RESULTS: We defined 3 types of petrosectomy: medial, inferior, and inferomedial. Medial petrosectomy was limited within the paraclival internal carotid artery (ICA) anteriorly, lacerum ICA inferiorly, abducens nerve superiorly, and petrous ICA laterally. Among those, abducens nerve and petrous ICA are surgical limits. Full skeletonization of the paraclival ICA and removal of the lingual process are essential for better access to the medial aspect of PA. Inferior petrosectomy was defined by the lacerum foramen synchondrosis anteriorly, jugular foramen inferiorly, internal acoustic canal posteriorly, and PA superolaterally. Those are surgical limits except for the foramen lacerum synchondrosis. The connective tissue at the pterygosphenoidal fissure was a key landmark for the sublacerum approach. Clinical cases in 3 types of PA lesions were presented. CONCLUSION: The EEA provides access to the medial and inferior aspects of the PA. Several technical maneuvers, including paraclival and lacerum ICA skeletonization, sublacerum approach, and lingual process removal, are key to maximize PA drilling.